An aliphatic hexene-covalent triazine framework for selective acetylene/methane and ethylene/methane separation. Issue 21 (14th May 2019) - Krishnaraj, Chidharth; Jena, Himanshu Sekhar; Leus, Karen; Freeman, Helen M.; Benning, Liane G.; Van Der Voort, Pascal
Abstract : Aliphatic hexene-covalent triazine framework for C2 /C1 hydrocarbon separation – dependence on morphology. Abstract : Unsaturated C2 hydrocarbons (acetylene and ethylene) are used in industries for various applications. These C2 hydrocarbons are produced through cracking processes, where, C1 hydrocarbons such as methane are usually present as a by-product. The conventional distillation process for C2 /C1 hydrocarbon separation uses a lot of energy and as such microporous adsorbents are widely studied as low energy alternatives. Herein, we present a novel hexene-covalent triazine framework (hexene-CTF) prepared from trans -3-hexenedinitrile (an aliphatic olefin type monomer) for high-performance acetylene/methane and ethylene/methane separation. The porosity, surface area and ordering of the materials were varied by changing the synthesis conditions. The characteristics of the material were characterized thoroughly by surface area analysis as well as transmission and scanning electron microscopy (TEM and SEM) measurements. The number of double bonds present within the CTF materials was determined by a bromine addition reaction. A high uptake of acetylene (3.85 mmol g −1 at 0 °C and 1 bar) was obtained. The presence of unsaturated double bonds in the hexene-CTF enhanced the interaction of the framework with the unsaturated double bond and triple bond of ethylene and acetylene respectively due to stronger pi–pi interactions. On the contrary, the saturated methane gas was not efficiently adsorbed, which resulted in a higher C2 /C1 selectivity. The calculated isosteric heat of adsorption showed a direct correlation between the gas uptake and the ordering in the hexene-CTF at low pressure regimes. This is the first example of a porous organic polymer which is capable of C2 /C1 hydrocarbon separation.